Embracing english as a lingua franca : learning from portuguese users of english in higher education - Pereira, Ricardo Jaime da Silva, 1973- (2016)
Tese de doutoramento, Linguística (Linguística Aplicada), Universidade de Lisboa, Faculdade de Letras, 2016